Mitochondria as metabolizers and targets of nitrite - Shiva, Sruti (2009)
Mitochondrial function is integral to maintaining cellular homeostasis through the production of ATP, the generation of reactive oxygen species (ROS) for signaling, and the regulation of the apoptotic cascade. A number of small molecules, including nitric oxide (NO), are well characterized regulators of mitochondrial function. Nitrite, an NO metabolite, has recently been described as an endocrine reserve of NO that is reduced to bioavailable NO during hypoxia to mediate physiological responses. Accumulating data suggests that mitochondria may play a role in metabolizing nitrite and that nitrite is a regulator of mitochondrial function. Here what is known about the interactions of nitrite with the mitochondria is reviewed, with a focus on the role of the mitochondrion as a metabolizer and target of nitrite.